1991
DOI: 10.1115/1.2897703
|View full text |Cite
|
Sign up to set email alerts
|

Elastic-Plastic Deformation in Surface-Cracked Plates: Experiment and Numerical Analysis

Abstract: Detailed three-dimensional nonlinear finite element (FE) analyses and experimental moire studies are performed on a plate containing a moderately deep part-through surface crack to establish limits of HRR-dominance. The plate is subjected to predominantly far-field tensile loading. The material under investigation is ASTM A710 steel, which was constitutively modeled by large deformation J2 flow theory of plasticity. The FE mesh was carefully constructed to resolve both crack front fields (such as J-integral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This confirms an earlier review by Parks [28] and agrees with the results discussed in [20,30,31] where FE analyses were compared with CTOA or CTOD measurements.…”
Section: Comparison Of Observed Hrr and Fe Fieldssupporting
confidence: 79%
See 3 more Smart Citations
“…This confirms an earlier review by Parks [28] and agrees with the results discussed in [20,30,31] where FE analyses were compared with CTOA or CTOD measurements.…”
Section: Comparison Of Observed Hrr and Fe Fieldssupporting
confidence: 79%
“…Indeed, it has been increasingly understood in the past decade that surface measurements are affected by 3-D effects [28][29][30], and that caution must be exercised in analysis of experimental data. For instance, it has been shown that plane-stress approximations are not sufficient to fit experimental measures such as the crack-tip opening angle (CTOA) or the crack-tip opening displacement (CTOD) (which are the surface measurements of crack-tip loading that are the most commonly performed), whereas 3-D analyses yield much better agreement [20,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain the total elastic-plastic strain field (and, in turn, the boundary with the crack-tip plastic zone) in elastoplastic materials other techniques are generally used, such as stereoimaging [18], Moir e interferometry [19,20], or laser-speckle interferometry [21][22][23]. By contrast, because photoelasticity provides only the elastic strain fields in the birefringent coating, it is mainly used to determine experimentally stress intensity factors for complex loading modes in components where the fields are predominantly linear elastic [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%